2016
DOI: 10.1021/acsphotonics.6b00272
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Radiation by Subpicosecond Magnetization Modulation in the Ferrimagnet LiFe5O8

Abstract: We report the terahertz radiation in the polar and ferrimagnetic insulating oxide LiFe5O8 upon irradiation of a femtosecond laser pulse at room temperature. By the resonant optical excitation of an originally spin-forbidden d–d transition in Fe3+ ions, we observed the emission of terahertz waves, which is attributable to the magnetic-dipole radiation originating from the light-induced subpicosecond magnetization modulation. By mapping out the emission of the terahertz waves, we successfully visualized the vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Figure 2 1mm-thick ZnTe crystal. By using terahertz radiation imaging [22][23][24][25][26], we confirmed that the BiTeBr crystal used in the present study has a polar single-domain structure. The result of the domain imaging is reported in the Supplemental Material [27].…”
supporting
confidence: 75%
“…Figure 2 1mm-thick ZnTe crystal. By using terahertz radiation imaging [22][23][24][25][26], we confirmed that the BiTeBr crystal used in the present study has a polar single-domain structure. The result of the domain imaging is reported in the Supplemental Material [27].…”
supporting
confidence: 75%
“…This effect of the ringing can be seen in several publications displaying the THz signal in the time and frequency domains. [25][26][27][28] The peak-to-peak amplitude of the THz signal (E THz ) in time-domain is measured for all CFA/Pt STEs and used as the dependent variable in Equation ( 3) with the CFA thickness as an independent variable. The explanation of Equation ( 3) is given in the following section.…”
Section: Resultsmentioning
confidence: 99%
“…Some additional properties such as strong Dzyaloshinskii-Moriya interaction lead to proposals for novel magnonic devices based on relativistic band engineering of LiFe crystals 25 . Besides microwave applications, the material is used for coatings of anodes for lithium ion batteries 26 , Terrahertz devices 27 and gas sensing 28 .…”
Section: Introductionmentioning
confidence: 99%